Analisis Penerapan Kecerdasan Majemuk (Multiple Intelligences) dalam Pembelajaran di Madrasah - Rizka Amalia; Nabilla Nabilla (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2024)
This research aims to analyze the multiple intelligence approach in teaching and education in madrasas. Gardner's theory of multiple intelligences provides a significant contrast to the models of mind that have traditionally been used to make a good teaching and learning. This study uses a qualitative descriptive approach with the type of library research. The results of this study indicate that the learning approach in madrasas that utilizes multiple intelligences can combine various aspects of intelligence, such as linguistic, intrapersonal, interpersonal and kinesthetic. Multiple intelligence-based learning strategies in madrasas involve several learning aspects aimed at fostering critical thinking skills through various learning methods that are adapted to the material presented.